Le corps au cœur de la prison coloniale au Dahomey (1894-1945) - Bénédicte Brunet-La Ruche (Les Cahiers de Framespa)
With the conquest of West Africa in the late 19th century, the prison became the main penalty as much as a colonial management tool, far from metropolitan penitentiary principles. For the French authorities, the “moral reform” objective was unattainable by Africans. Confinement first and foremost aims at punishing and using the body. This article aims at understanding the experience of imprisoned bodies in Dahomey. The first prison experience was that of a drop in what wass called the “box”: a suffocating box, where prisoners did not even have the vital minimum and where a certain level of violence was tolerated. But the daily use of penal labor outside the prison and the lack of resources also made the prison an open “box”, with constant back and forth between the inside and the outside organized by guards, prisoners, and the Dahomeyan population.